2018
DOI: 10.3762/bjoc.14.7
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent nucleobase analogues for base–base FRET in nucleic acids: synthesis, photophysics and applications

Abstract: Förster resonance energy transfer (FRET) between a donor nucleobase analogue and an acceptor nucleobase analogue, base–base FRET, works as a spectroscopic ruler and protractor. With their firm stacking and ability to replace the natural nucleic acid bases inside the base-stack, base analogue donor and acceptor molecules complement external fluorophores like the Cy-, Alexa- and ATTO-dyes and enable detailed investigations of structure and dynamics of nucleic acid containing systems. The first base–base FRET pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 83 publications
1
17
0
1
Order By: Relevance
“…In the past decades, a number of fluorescent nucleobase analogs (FBAs) have been reported and applied for studies of RNA structure and folding, including isomorphic and isofunctional heterocycles in an emissive RNA alphabet . FRET pairs of FBAs have attracted increasing interest because the readout is not limited to a single position . The rigid placement of isomorphic FBAs inside double‐stranded DNA/RNA resulted in FRET efficiencies close to theoretically predicted values and enabled their use as molecular rulers .…”
Section: Figuresupporting
confidence: 62%
“…In the past decades, a number of fluorescent nucleobase analogs (FBAs) have been reported and applied for studies of RNA structure and folding, including isomorphic and isofunctional heterocycles in an emissive RNA alphabet . FRET pairs of FBAs have attracted increasing interest because the readout is not limited to a single position . The rigid placement of isomorphic FBAs inside double‐stranded DNA/RNA resulted in FRET efficiencies close to theoretically predicted values and enabled their use as molecular rulers .…”
Section: Figuresupporting
confidence: 62%
“…In the B‐form structure, the angle between the helical axis and the fluorescent nucleobase is almost 90° in the cylinder model of the DNA duplex because of the fixed parallel plan of the fluorescent nucleobase caused by hydrogen bonding with the counterbase and stacking interaction between neighboring bases, indicating that κ 2 can be assumed to between 0 and 1 . On the other hand, the base pair of the DNA duplex in the nucleosome undergoes geometrical changes such as roll, tilt, and twist unlike typical B‐form DNA .…”
Section: Resultsmentioning
confidence: 99%
“…[25][26][27][28][29][30][31] After minimizationo f th dG and tC-containing nucleosome structure, the In the B-form structure,t he angle between the helicala xis and the fluorescent nucleobase is almost 908 in the cylinder model of the DNA duplex because of the fixed parallel plan of the fluorescent nucleobase caused by hydrogen bonding with the counterbase and stacking interaction between neighboring bases, indicating that k 2 can be assumed to between 0a nd 1. [20,41,42] On the other hand, the base pair of the DNA duplex in the nucleosome undergoes geometrical changes such as roll, tilt, and twist unlike typical B-form DNA. [24,43] Geometrical features of DNA bases on nucleosome, such as pseudo-twofold axis and propeller twist between base pairs, can provide a wide range of orientation factors (k 2 = 0t o4 ).…”
Section: Resultsmentioning
confidence: 99%
“…21 Since its first report, Wilhelmsson and collaborators have extended the variety of fused aromatic ring adenine analogs greatly and have shown that they are bright and tunable fluorophores and have employed them in FRET-based probes. 22,23,24,25 Given the structural similarity between the carbazole cytosine analog (a benzofused pyrrolocytosine) and pyrrolocytosine ( Figure 2b), which is obtained via Larock-type cyclization 26 of 5-alkynylcytosine derivatives, we reasoned that a tricyclic adenine analog derived from the 7-deaza-7-alkynyladenine may possess useful and interesting fluorescence. This approach was attractive because such adenine analogs are derived from readily available and diverse alkynes.…”
Section: R a F Tmentioning
confidence: 99%